Growth of the common bean submitted at different levels of water deficit in the soil - da Silva Martins, Camila Aparecida; Fialho dos Reis, Edvaldo; de Oliveira Garcia, Giovanni (REVISTA DE AGRICULTURA, 2018)
The objective of this study was to evaluate the effect of water deficit on the growth of common bean cultivated in medium and clayey soil. Two experiments were developed in factorial scheme of 2 x 4 with tension for the determination of field capacity on two levels and soil water deficit on four levels in a completely randomized design with three replicates for each soil. Growth analyzes were performed in two phenological stage of crop and the data were submitted to an analysis of variance (p â‰¤ 0.05). When significant, the F Test (p â‰¤ 0.05) was used for the qualitative factor and regression analysis for the quantitative factor. The water content in the soil of 40 and 60% of available water exerted negative effects on leaf water potential, leaf area and total dry matter of the common bean, independent of voltage adopted in determining the field capacity.